High-Contrast Frontend for Petawatt-Scale Lasers Using an Optically Synchronized Picosecond Optical Parametric Chirped Pulse Amplification - Hao Xue; Meizhi Sun; Linjun Li; Lijuan Qiu; Zhantao Lu; Xinglong Xie; Guoli Zhang; Xiao Liang; Ping Zhu; Xiangbing Zhu; Qingwei Yang; Ailin Guo; et al. (Photonics, 2022)
We present a new scheme of picosecond optical parametric chirped pulse amplification (OPCPA) in which a Fourier-transform-limit 5.0 ps pulse is optically sheared from a single-longitudinal-mode 1064 nm CW laser. The pulse is amplified and frequency-doubled as the pump in order to maintain the pump narrow bandwidth and picosecond duration simultaneously, which is very important to ensure the high temporal contrast for an OPCPA amplifier. Combined with the cross-polarized wave generation (XPW), a compound frontend for the high-power femtosecond laser system that delivers a 1 Hz chirped pulse train is established. The experiments provide an output pulse energy of 17.1 mJ, a spectrum bandwidth 71 nm (FWHM), and a pulse duration 16.4 fs. The pulse contrast reaches 1:10−12 several picoseconds before the peak of the main pulse, which is the best value of the available measuring instruments.